Challenges and Future Visions of the Hungarian Livestock Sector from a Rural Development Viewpoint - Jenő Zsolt Farkas; Irén Rita Kőszegi; Edit Hoyk; Ádám Szalai (Agriculture, 2023)
Livestock farming in developed countries faces adverse environmental impacts, including greenhouse gas emissions and pollution. Moreover, economic and social issues have emerged, such as farm concentration and the aging of farmers. Consequently, the decline of small farms and household animal husbandry substantially impacted rural communities, posing challenges for rural development. This study investigates these processes within the Hungarian livestock sector from the 1990s to recent years in the context of rural development, which is a rarely explored viewpoint in the literature. The research employed a statistical and policy document analysis, a literature review, and interviews (n = 66) conducted in Hungary’s Southern Great Plain region. The results reveal a decline in the number of animals and small farms in rural settlements, accompanied by an intense farm concentration, negatively affecting income generation opportunities. The established large-scale industrial animal husbandry has adverse environmental effects without positive externalities. The interviews highlight the severe challenges that young farmers face in starting their businesses, including land, labor, and capital shortages, leading to a slow generational change in the farming society. These processes demonstrate the limited multifunctionality of animal husbandry in Hungary. Our findings differ from those advocating for large-scale industrial agriculture development because an overly one-sided development pathway could lead to unsustainability.